Preparation and Characterization of Interfacially Polymerized Polyamide Membrane for Dye Removal - Himma, Nurul Faiqotul; Ismuyanto, Bambang; Hidayati, AS; Juliananda, Juliananda; Rohmawati, Hidayatul; Budiarta, Irfan (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2021)
Interfacial polymerization of polyamide was conducted using hydrophobic and hydrophilic membrane support. The effects of monomer concentration were investigated, and the resulting thin-film composite membranes were tested for their performance in dye removal using different flow configurations. The results showed that a dense polyamide layer was successfully formed on the hydrophilic support, while a polyamide layer with a very loose structure was formed on the hydrophobic support. The polyamide layer became smoother and more hydrophilic as the concentration of trimesoyl chloride was increased, leading to increased permeate flux and reduced dye rejection. The highest sunset yellow rejection of 45.7% with a permeate flux of 4.9 L/m2.h was obtained when the polyamide layer was formed from trimesoyl chloride concentration of 0.05 w/v% (a high amine to acid chloride monomer ratio of 20) and the filtration was in cross-flow configuration.